Case report: Ultrasound diagnosis of a complicated case of gastric lymphoma misdiagnosed as cirrhosis - Yang, Dayan; Gao, Lini (Frontiers in Oncology, 2024)
The gastrointestinal (GI) tract is the most common primary site for extranodal lymphomas. The use of ultrasonography for diagnosing gastric lymphomas can be challenging, but ultrasonography still offers some unique advantages in the diagnosis of GI lymphomas. Here, we report a case of gastric lymphoma in a patient with an extensive lesion in which the tumor was complexed with the abdominal organs. CT and endoscopy failed to definitively diagnose the condition in a timely manner.The gastric lymphoma was finally diagnosed with ultrasonography and a treatment plan was implemented.